Air pollution and violent criminal behaviour - Cruz, Erik (The British journal of criminology, 2022)
This study advances the literature by examining the effect of carbon monoxide emissions on the degree of physical violence exhibited by a criminal offender during the commission of a criminal offense. A multilevel analysis is conducted to probe the relationship between carbon monoxide levels and whether a criminal offender physically injures his or her victim. The offender-level data are drawn from the National Incident-Based Reporting System and represent 139,709 single offender/single victim crime incidents for 109 cities in 22 states during 2015. Carbon monoxide concentration and city-level contextual control variables are drawn from other sources. Results show that while carbon monoxide emissions have little effect on the overall level of physical violence displayed by a criminal offender, both the offender’s race and sex moderate the relationship between air pollution and victim injury. As carbon monoxide levels rise in a city, both black and male offenders are more likely to injure their victims physically. We theorize that black and male offenders are more vulnerable to the violence-inducing effects of air pollution because of pronounced racial and sex differences in carbon monoxide exposure.